3D reconstructions of the ceramic assemblages of hunter-gatherers from the Northeastern coast of Chubut, Argentine Patagonia - Schuster, Verónica; Quinto Sánchez, Mirsha (Instituto de Arqueología, Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2019)
The main aim of this article is to serve as an introduction to the use of a method not previously employed in the study of the pottery of hunter-gatherer groups from Patagonian Argentina: the three-dimensional (3D) virtual reconstruction of partially assembled containers. In the archaeological contexts of the study area —northeastern coast of the Chubut province— the ceramic material is highly fragmented, and although some potsherds were partially assembled, complete representations of the different morphologies were not documented prior to the application of this method. In this regard, our paper shows the technical-methodological procedure by which the virtual graphic images were obtained in 3D. Furthermore, we also discuss the data resulting from this analysis, information relating to the volume —or capacity— and weight of the ceramic pieces. As an initial interpretative tool, these variables allow us to propose concepts related to the use and transportation of these containers.